2020
DOI: 10.5194/bg-17-4961-2020
|View full text |Cite
|
Sign up to set email alerts
|

Protists and collembolans alter microbial community composition, C dynamics and soil aggregation in simplified consumer–prey systems

Abstract: Abstract. Microbes play an essential role in soil functioning including biogeochemical cycling and soil aggregate formation. Yet, a major challenge is to link microbes to higher trophic levels and assess consequences for soil functioning. Here, we aimed to assess how microbial consumers modify microbial community composition (PLFA markers), as well as C dynamics (microbial C use, SOC concentration and CO2 emission) and soil aggregation. We rebuilt two simplified soil consumer–prey systems: a bacterial-based sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 98 publications
(123 reference statements)
1
22
0
Order By: Relevance
“…Soil type is already known to affect the composition and ratio of smaller and larger predators [ 75 , 76 ]. Moreover, it has been suggested that different pore sizes in soils are main drivers of compartmentalization of different prey and predator organisms [ 77 ]. Thus, microorganisms inhabiting non-continuous capillary pores could be protected from predation by protists and Nematoda , but not from the similarly-sized myxobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Soil type is already known to affect the composition and ratio of smaller and larger predators [ 75 , 76 ]. Moreover, it has been suggested that different pore sizes in soils are main drivers of compartmentalization of different prey and predator organisms [ 77 ]. Thus, microorganisms inhabiting non-continuous capillary pores could be protected from predation by protists and Nematoda , but not from the similarly-sized myxobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis also revealed that these effects on bacterial community structure were likely due to individual bacterial taxa differentially responding to protist density and size ( Figure 4B ), thus suggesting that strong size-dependencies may be at play. Previous studies have shown that protist predation can select for bacterial size ( Hahn and Höfle, 2001 ; Pernthaler, 2005 ; Erktan et al, 2020 ), and both negative and positive associations with different protists have also been shown ( Oliverio et al, 2020 ). In addition to the direct predator effects on responding bacterial taxa, we cannot rule out indirect effects of the predator presence—due to higher order interactions—to explain the abundance shifts of certain responding bacteria ( Karakoç et al, 2018 ; Mickalide and Kuehn, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These global maps represent a step forward in clarifying the role of feeding interactions in the temperature responses of microbial communities. However, with a global biomass 200 times larger than that of nematodes ( Bar-On et al, 2018 ), unicellular eukaryotes—collectively known as “protists”—likely play a major role in regulating microbial communities at global scales ( Oliverio et al, 2020 ) through bacterivory ( Gao et al, 2019 ; Erktan et al, 2020 ). Ciliate protists, in particular, are well-known bacterivores ( Foissner and Berger, 1996 ), their population dynamics and feeding interactions are strongly temperature-dependent ( DeLong and Lyon, 2020 ), and they are present in all major ecosystems ( Foissner and Berger, 1996 ; Oliverio et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that protist predation can select for bacterial size (Erktan et al, 2020;Hahn & Höfle, 2001;Pernthaler, 2005), and both negative and positive associations with different protists have also been shown (Oliverio et al, 2020). In addition to the direct predator effects on responding microbial taxa, we cannot rule out indirect effects of the predator presence, due to higher order interactions to explain the abundance shifts of certain responding microbes (Karakoç et al, 2018;Mickalide & Kuehn, 2019).…”
Section: Discussionmentioning
confidence: 88%
“…These global maps represent a step forward in clarifying the role of feeding interactions in the temperature responses of microbial communities. However, with a global biomass 200 times larger than that of nematodes (Bar-On et al, 2018), unicellular eukaryotes -collectively known as 'protists' -likely play a major role in regulating microbial communities at global scales (Oliverio et al, 2020) through bacterivory (Erktan et al, 2020;Gao et al, 2019). Ciliate protists, in particular, are wellknown bacterivores (Foissner & Berger, 1996), their population dynamics and feeding interactions are strongly temperature-dependent (DeLong & Lyon, 2020), and they are present in all major ecosystems (Foissner & Berger, 1996;Oliverio et al, 2020).…”
Section: Introductionmentioning
confidence: 99%